Influence of laser power and scanning speed on microstructure evolutions and mechanical properties of the SLM fabricated Al–Mg–Mn–Sc–Zr alloy - Mengmeng Tong; Huidi Zhang; Chun Chen; Jianfei Hao; Zhiping Chen; Fuzhu Wang; Runxia Li; Biao Wang (Journal of Materials Research and Technology)
The Al–Mg–Mn-Sc-Zr alloy is fabricated by selective laser melting (SLM). The influence of laser power and scanning speed on microstructure evolutions and mechanical properties is studied in this research. Results indicate that increasing laser power can refine grain structures and reduce anisotropy on the printing surface. However, the increase in laser power will enhance the residual stress inside the alloy, leading to a decrease in elongation. The scanning speed affects the molten pool energy input and cooling rate. When the scanning speed is between 750mm/s-1250 mm/s, the alloy achieves a good grain refinement effect and weak texture strength. In addition, there exists a large number of nano-scaled Al3(Sc,Zr) particles precipitated during solidification and the subsequent annealing process, which can significantly enhance yield strength of the alloy. Overall, the Al–Mg–Mn-Sc-Zr alloy has a wide SLM forming window. When the laser power ranges from 200 W to 250 W, the scanning speed ranges from 750 mm/s to 1250 mm/s, and the volume energy density ranges from 80 J/mm3 to 130 J/mm3, the Al–Mg–Mn-Sc-Zr alloy can obtain good formability and mechanical property.